Evidence of parasympathetic hyperactivity in functionally overreached athletes - Le Meur, Y.; Pichon, A.; Schaal, K.; Schmitt, L.; Louis, J.; Gueneron, J.; Vidal, P. P.; Hausswirth, C. (Medicine & Science in Sports & Exercise, 2014)
Purpose: We analyzed HR variability (HRV) to detect alterations in autonomic function that may be associated with functional overreaching (F-OR) in endurance athletes. Methods: Twenty-one trained male triathletes were randomly assigned to either intensified training (n = 13) or normal training (n = 8) groups during 5 wk. HRV measures were taken daily during a 1-wk moderate training (baseline), a 3-wk overload training, and a 1-wk taper. Results: All the subjects of the intensified training group demonstrated a decrease in maximal incremental running test performance at the end of the overload period (-9.0% ± 2.1% of baseline value) followed by a performance supercompensation after the taper and were therefore diagnosed as F-OR. According to a qualitative statistical analysis method, a likely to very likely negative effect of F-OR on HR was observed at rest in supine and standing positions, using isolated seventh-day values and weekly average values, respectively. When considering the values obtained once per week, no clear effect of F-OR on HRV parameters was found. In contrast, the weekly mean of each HRV parameter showed a larger change in indices of parasympathetic tone in the F-OR group than the control group in supine position (with a 96%/4%/0% chance to demonstrate a positive/trivial/negative effect on Ln RMSSD after the overload period; 77%/22%/1% on LnHF) and standing position [98%/1%/1% on Ln RMSSD; 99%/0%/1% on LnHF; 95%/1%/4% on Ln(LF + HF)]. During the taper, theses responses were reversed. Conclusions: Using daily HRV recordings averaged over each week, this study detected a progressive increase in the parasympathetic modulation of HR in endurance athletes led to F-OR. It also revealed that due to a wide day-to-day variability, isolated, once per week HRV recordings may not detect training-induced autonomic modulations in F-OR athletes.